Factors that influence the employee retention in Majlis Agama Islam Negeri Sembilan and Majlis Agama Islam Melaka / Nur Hidayah Roslan - Roslan, Nur Hidayah (Faculty of Business and Management, 2013)
Employee’s retention is very important things in ones organization that can helps in their survival, productivity, profitability and to run the organization effectively. It is a continuous challenge for managers because it is hard to fulfil all employees’ needs and to satisfy them in the organization. When an individual feel unsatisfied and unmotivated to stay in the organization they work for, they tend to move to the other organization. So, the purpose of this study is to identify the relationship between the opportunity for growth, equity of compensation, fairness, employee’s satisfaction and availability of technology facilities with the employee’s retention. The data has been collected from employees at Majlis Agama Islam Melaka (MAIM) and Majlis Agama Islam Negeri Sembilan (MAINS) by distributing the questionnaires to 39 employees in the both organization, where 30 employees in Majlis Agama Islam Melaka and 9 employees in Majlis Agama Islam Negeri Sembilan respectively that been selected randomly. After the data have been analyzed, the result showed that, there is significance correlation relationship between the hygiene factors with the employee’s retention. This study also said to be beneficial to both organization in order to retain their employees. At the end of this research, some of the recommendations are also having been discussed.